Handbook of Development Economics : Vol. 5 - Rodrik, Dani; Rosenzweig, Mark R. (Amsterdam : Elsevier, 2010)
Annotation This handbook organizes chapters by sets of policies that are important components of discussions about how to facilitate development. In each chapter, authors identify and discuss the relevant theoretical and empirical literature that describes the fundamental problems that the policies seek to remedy or ameliorate, as well as the literature that evaluates the effects of the policies.* Presents an accurate, self-contained survey of the current state of the field* Summarizes the most recent discussions, and elucidates new developments* Although original material is also included, the main aim is the provision of comprehensive and accessible surveys
Scholarly & Professional
Keywords: Economic development -- Handbooks, manuals